2020
DOI: 10.1097/md.0000000000023595
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of a lipoma arborescens of the elbow

Abstract: Introduction: Lipoma Arborescens is a rare pathology that mainly affects the knee. Occurrences in the elbow are even more uncommon and mainly involve the bicipitoradial bursa. Case's description: We describe the case of a 54-year-old patient known for rheumatoid arthritis, who consulted for chronic elbow pain associated with swelling and limited extension. Diagnosis: The diagnosis of a lipoma arborescens of the elbow involving the whole joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
“…All patients had single lesion; one has a bilateral presentation [ 26 ]. Eleven lesions (50%) were located in the shoulder [ 1 3 , 22 , 24 , 28 , 30 , 32 , 33 , 35 , 36 ], seven (31.82%) in the elbow [ 13 , 23 , 25 , 26 , 29 , 34 ], and four (18.18%) in the wrist [ 14 , 27 , 31 , 37 ]. All patients but one had preoperative MRI scans during the diagnostic assessment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirming lipoma arborescens is based on macroscopic appearance after resection [ 12 ]. The gross appearance of lipoma arborescens confirms radiologic findings, showing a frond-like or finger-like lipomatous proliferation [ 14 ].…”
Section: Discussionmentioning
confidence: 70%